Community stakeholder structural perception of firms’ environmental disclosure level in Nigeria: Environmental accounting disclosure in Nigeria - Afrogha, Olufolake; Doorasamy, Mishelle; Akintoye, Ishola Rufus; Akande, Joseph Olorunfemi (The Journal of Accounting and Management, 2022)
Given the slow progress towards the achievement of Agenda 2030 and the environmentally sustainable development goals (SDGs), this study investigates the perception of communities’ environmental disclosure activities of the firms operating in their domain. Data were surveyed by means of a closed-ended questionnaire from 157 community respondents from the four most industrialised cities in Nigeria. The data were analysed using the Chi-square test for association and the confirmatory factor analysis. The results revealed that both firms’ environmental activities, environmental reporting, and environmental reporting benefits collectively shape the community perception of the activities of firms on the environment. Furthermore, the study revealed that there is no association between respondents’ level of education and their perception about environmental disclosure of firms in their community. Implying that communities’ knowledge of the environmental activities of firms is not dependent on their education level. These findings highlighted community stakeholders’ concerns about the activities of companies within their environment and their awareness, feeding into the power of Ullmann’s stakeholder framework. Such could be harnessed to improve firms’ environmental footprints, hence the progress towards actualizing the environmental SDGs.